Genetic diversity and structure of Ganoderma boninense isolates from oil palm and other plantation crops - AGUSTIAMAN PURBA; RAHMAH HAYATI; LOLLIE A.P. PUTRI; DIANA CHALIL; INDRA SYAHPUTRA; Mohammad Basyuni (Society for Indonesian Biodiversity, 2020)
Abstract. Purba A, Hayati R, Putri LAP, Chalil D, Afandi D, Syahputra I, Basyuni M. 2020. Genetic diversity and structure of Ganoderma boninense isolates from oil palm and other plantation crops. Biodiversitas 21: 451-456. Oil palm is an economically important plant, which one of the most important sources of vegetable oil in the world. However, oil palm plantation and other crops face the treat basal stem rot (BSR) disease by Ganoderma boninense. A study on genetic diversity and structure of G. boninense is therefore needed in order to formulate improved control strategies for this disease. This work aimed to analyze the genetic diversity and structure of the G. boninense isolates derived from different hosts, 131 oil palm (Elaeis guineensis), six rubber (Hevea brasiliensis), three coconuts (Cocos nucifera), and three lontar palm (Borassus flabellifer). Genetic diversity and population structure of G. boninense isolates were investigated using six SSR markers with GenAlex 6.502 software. Results showed that several microsatellite loci indicated specific primary success rates, such as KT124402, KT124399, and KT124394, depicting high polymorphism content (>75%). This result suggested that these markers were equally effective in determining the polymorphisms of G. boninense isolates. A hierarchical analysis of molecular variance (AMOVA) revealed that genetic diversity mostly found among individuals within a population (88%), then among populations (8%), and within individuals (4%).. Phylogeny analysis showed two clusters of Ganoderma isolates. which was considered variation as dissimilar across with origin. The present study indicated that G. boninense from oil palm was predominantly comprised of a genetically distinct individual.